Addressing Systematics in the Traceback Age of the β Pictoris Moving Group - Dominic Couture; Jonathan Gagné; René Doyon (The Astrophysical Journal, 2023)
We characterize the impact of several sources of systematic errors on the computation of the traceback age of the β Pictoris moving group ( β PMG). We find that uncorrected gravitational redshift and convective blueshift bias absolute radial velocity measurements by ∼0.6 km s ^−1 , which leads to erroneously younger traceback ages by ∼2 Myr. Random errors on parallax, proper motion, and radial velocity measurements lead to an additional bias of ∼0.6 Myr on traceback ages. Contamination of astrometric and kinematic data by kinematic outliers and unresolved multiple systems in the full input sample of 76 members and candidates of β PMG also erroneously lowers traceback ages by ∼3 Myr. We apply our new numerical traceback analysis tool to a core sample of 25 carefully vetted members of β PMG using Gaia Data Release 3 data products and other kinematic surveys. Our method yields a corrected age of 20.4 ± 2.5 Myr, bridging the gap between kinematic ages (11–19 Myr) and other age-dating methods, such as isochrones and lithium depletion boundary (20–26 Myr). We explore several association size metrics that can track the spatial extent of β PMG over time, and we determine that minimizing the variance along the heliocentric curvilinear coordinate ${ξ }^{{′} }$ (i.e., toward the Galactic Center) offers the least random and systematic errors, due to the wider UVW space velocity dispersion of members of β PMG along the U -axis, which tends to maximize the spatial growth of the association along the ${ξ }^{{′} }$ -axis over time.